The Heterogeneity of Inflammatory Response and Emphysema in Chronic Obstructive Pulmonary Disease - Xu, Xia; Huang, Ke; Dong, Fen; Qumu, Shiwei; Zhao, Qichao; Niu, Hongtao; Ren, Xiaoxia; Gu, Xiaoying; Yu, Tao; Pan, Lin; Yang, Ting; Wang, Chen (Frontiers in Physiology, 2021)
Chronic obstructive pulmonary disease (COPD) is a heterogeneous disease characterized by chronic inflammation, emphysema, airway remodeling, and altered lung function. Despite the canonical classification of COPD as a neutrophilic disease, blood and airway eosinophilia are found in COPD patients. Identifying the tools to assess eosinophilic airway inflammation in COPD models during stable disease and exacerbations will enable the development of novel anti-eosinophilic treatments. We developed different animal models to mimic the pathological features of COPD. Our results show that eosinophils accumulated in the lungs of pancreatic porcine elastase-treated mice, with emphysema arising from the alveolar septa. A lipopolysaccharide challenge significantly increased IL-17 levels and induced a swift change from a type-2 response to an IL-17-driven inflammatory response. However, lipopolysaccharides can exacerbate cigarette smoking-induced airway inflammation dominated by neutrophil infiltration and airway remodeling in COPD models. Our results suggest that eosinophils may be associated with emphysema arising from the alveolar septa, which may be different from the small airway disease-associated emphysema that is dominated by neutrophilic inflammation in cigarette smoke-induced models. The characterization of heterogeneity seen in the COPD-associated inflammatory signature could pave the way for personalized medicine to identify new and effective therapeutic approaches for COPD.